Social networks and quality of life in relation to university students’ health - Hanna Lavalle, Monica Isabel; Ocampo Rivero, Mónica Mabel; Janna Lavalle, Nadya María; Mena Gutiérrez, María Carolina; Torreglosa Portillo, Leydi Diana (Revista Cuidarte, 2020)
Introduction: Social networks provide young people with the opportunity to be in touch with society and their environment, for which they spend a great amount of time to seek acceptance from their peers. Materials and Methods: A cross-sectional descriptive correlational study was conducted on a sample of 400 students. Two questionnaires were used to collect information. For variable comparison, Spearman’s rank correlation coefficient and Chi-squared test were used. Results: 354 (88.5%) of university students have a mobile device with internet connection; 184 (46%) use 3 to 4 social networks and 196 (49%) use them for about 1 to 4 hours a day. 157 (39.2%) claimed that their studies were not affected by using social networks. As for general health, Colombians scored 58.5 and Mexicans 38.3 on a scale of 0 to 100. Discussion: Young people spend most of their time using social networks, being particularly interested in social relationships with their peers. Some studies suggest an association between internet misuse and physical and psychosocial health problems. Conclusions: Social network use behavior and quality of life perception are similar in Colombia and Mexico. In addition, social networks are moderately used as an academic and socialization tool. There is a need for opportunities to share with peers in which social networks are not used as a mediator.Como citar este artículo: Hanna MI, Ocampo MM, Janna NM, Mena MC, Torreglosa LD. Redes sociales y calidad de vida relacionada con la salud en estudiantes universitarios. Rev Cuid. 2020; 11(1): e953. http://dx.doi.org/10.15649/cuidarte.953
Keywords: Adolescent; Quality of Life; Behavior; Students; Social Networking